Isang Panimulang Sosyolohikal na Pagtingin sa Pamamahala ng Laguna de Bai sa Konteksto ng Pagbaha: Pokus sa mga Bayan ng Pakil at Santa Cruz - Miranda, Praksis A. (Philippine Social Sciences Review; Volume 64, No. 1, Jan-Jun 2012, Ed. Eric Manalastas, 2012)
In light of the recent flooding in Laguna towns caused by the overflow of Laguna de Bai during the onslaught of typhoons Ondoy, Pepeng and Santi, questions were raised by the media and the public as to how such a disaster could have been prevented. Who were managing the lake and its regions? Or, what institutions are directly involved in managing the lake? Was there inability or negligence on the part of the said institutions managing the lake? This paper seeks to answer these questions through the sociological lens – guided by Parsons’ social systems theory, particularly the AGIL framework. The results of the study show that new institutions are needed which will perform the Integration function of the entire lake system (lake police force and environment police force). There is also a need for a supplemental budget for the LLDA so that the Adaptation function of the entire lake system can be carried out. The participation of the media and the local community in the performance of the Latency function for the entire system is also important – they can undertake massive environmental awareness campaigns about the lake as an ecological resource. Thus, Parsons’ AGIL scheme aided in shedding light to the recurring problems of lake management which are related to its current flooding, and that such problems are possibly rooted in the need to establish new institutions in each of the lake’s subsystems. Through Parsons’ AGIL framework, this study can enlighten policymakers and lake administrators on possible institutional changes that can be undertaken so as to maintain the ecological balance of the lake and prevent future displacement of the people living in the lake’s nearby towns due to flooding, and contribute to the growing literature on environmental sociology, sociology of disaster and disaster management.
Keywords: flood